2002
DOI: 10.1080/11250000209356480
|View full text |Cite
|
Sign up to set email alerts
|

Actiniaria and Scleractinia (Cnidaria, Anthozoa) from the Adriatic Sea (Croatia): First records, confirmed occurrences and significant range extensions of certain species

Abstract: Among the Anthozoa collected in recent years from Croatian waters, two species of Actiniaria and eight species of Scleractinia (from 21 stations) deserve special mention. Here we document the first records in the Adriatic Sea of the actiniarians Alicia mirabilis and Halcampoides purpurea and the scleractinians Coenocyathus cylindricus, Spbenotrochus andrewianus and Balanophyllia regia, while the previously uncertain occurrence in this part of the Mediterranean Sea is confirmed for the first time for the sclera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 7 publications
(16 reference statements)
3
27
0
Order By: Relevance
“…A. calycularis is found at depths of 0Á50 m (Rossi 1971), but is typically found in the shallow infralittoral (0Á15 m depth), on vertical walls or inside caves (Kruzic et al 2002). It is an azooxanthellate species (Cairns 1999), living in both light and dark and seems to prefer elevated hydrodynamism (Kruzic et al 2002). The population density can be high, with colonies covering up to 90% of the bottom (personal observations).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A. calycularis is found at depths of 0Á50 m (Rossi 1971), but is typically found in the shallow infralittoral (0Á15 m depth), on vertical walls or inside caves (Kruzic et al 2002). It is an azooxanthellate species (Cairns 1999), living in both light and dark and seems to prefer elevated hydrodynamism (Kruzic et al 2002). The population density can be high, with colonies covering up to 90% of the bottom (personal observations).…”
Section: Introductionmentioning
confidence: 99%
“…The colonies generally have an ellipsoid shape with polyps densely crowded or separated, depending on flow (Kruzic et al 2002). Near the surface (high hydrodynamism), massive-shaped colonies have polyps with a polygonal calyx (Kruzic et al 2002). In these colonies the new polyps bud both in the outskirts of the colonies and between existing polyps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It inhabits rocky shores from the surface to 50 m depth (Rossi 1971, Ocaña et al 2000 but is typically found in the shallow infralittoral zone (0 to 15 m depth), on vertical walls or inside caves (Cinelli et al 1977, Zibrowius 1978, Kružic et al 2002. It occupies both light and dark environments and appears to prefer a high hydro dynamism (Cinelli et al 1977, Zibrowius 1978, 1995, Kružic et al 2002.…”
Section: Introductionmentioning
confidence: 99%